2005
DOI: 10.1097/01.mph.0000158531.12996.38
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Metastatic Site at Diagnosis in Wilms?? Tumor

Abstract: The purpose of this study was to identify the prognostic significance of pulmonary and liver involvements present at diagnosis in children with Wilms' tumor. From 1971 to 2002, 57 patients with stage IV Wilms' tumor were diagnosed, treated, and followed in the authors' institution. Metastases were detected by chest radiography, abdominal ultrasonography, and/or thoracoabdominal computed tomography. Nephrectomy with tumor resection was performed and appropriate chemotherapy was given to all the patients. The Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…Varan et al reported poor outcomes of patients with liver metastases. 6 This single institutional report included 542 patients treated over thirty years, 57 of whom had stage IV disease, including 18 with liver metastases. The overall survival rate was 50.2% for those with lung metastases compared to 16.6% for those with liver metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Varan et al reported poor outcomes of patients with liver metastases. 6 This single institutional report included 542 patients treated over thirty years, 57 of whom had stage IV disease, including 18 with liver metastases. The overall survival rate was 50.2% for those with lung metastases compared to 16.6% for those with liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…25 Recent reports, however, suggested that liver involvement at diagnosis in infants and children with Wilms tumor indicated a worse prognosis than lung or other sites of Stage IV disease. 68 The International Society of Pediatric Oncology (SIOP) and the German Pediatric Oncology Group (GPOH) studied 29 patients with liver metastases at diagnosis, including some adult patients with Wilms tumor. 7 The overall survival was less than 60%, but all patients who had complete resection of the hepatic lesions survived.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the presence or absence of lung nodules does not affect the treatment plan in the early stages, a lung CT is not necessary [39]. The survival of the patients with metastasis from the right kidney is worse than the survival of those with metastasis from the left kidney [40]. …”
Section: Histopathologymentioning
confidence: 99%
“…The most common sites of recurrence are the lungs, pleura, tumor bed, and the liver. Among all patients with Wilms’ tumor, those with liver involvement have a poorer prognosis than those with lung metastasis [40, 71]. …”
Section: Prognosismentioning
confidence: 99%